2017
DOI: 10.3389/fnbeh.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Focused and Sustained Attention Is Modified by a Goal-Based Rehabilitation in Parkinsonian Patients

Abstract: Rehabilitation for patients with Parkinson’s disease (PD) is based on cognitive strategies that exploit attention. Parkinsonians exhibit impairments in divided attention and interference control. Nevertheless, the effectiveness of specific rehabilitation treatments based on attention suggests that other attentional functions are preserved. Data about attention are conflicting in PD, and it is not clear whether rehabilitative treatments that entail attentional strategies affect attention itself. Reaction times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…Consistent with this evidence, we have have demonstrated that an intensive and aerobic rehabilitation treatment such as MIRT promotes a beneficial effect on the executive component of attention in patients with PD. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this evidence, we have have demonstrated that an intensive and aerobic rehabilitation treatment such as MIRT promotes a beneficial effect on the executive component of attention in patients with PD. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Cognition is improved by specific motor trainings (David et al, 2015; Ferrazzoli et al, 2017), and it has been showed how the improvement in cognitive functioning may be considered as an index of neuroplasticity (Hötting and Röder, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The main feature of the disease is the impaired ability to learn and express habitual-automatic actions [ 43 45 ]: since DRT does not improve the expression of habitual-automatic actions in Parkinsonian subjects, the main goal of rehabilitation should be properly the re-learning of the lost habitual motor behaviours. In fact, even though their habitual scheduling is altered [ 43 ], the parkinsonian subjects can still express habitual skills by using the executive-volitional component of action [ 28 , 46 49 ]. For this reason, in the field of PD rehabilitation, external stimuli and specific techniques and strategies [ 28 , 34 36 , 50 ] have been properly developed in order to perform motor actions in a volitional and goal-directed manner [ 13 , 14 , 28 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the improvements in motor performances after MIRT cannot be explained only by these “activity-dependent” processes. The goal-directed approach of this kind of multidisciplinary and intensive rehabilitation is another fundamental requirement for achieve motor-functional improvements [ 49 ]. The physical techniques, the devices and the cognitive strategies adopted in this rehabilitative protocol, exploit the functions of the frontal cortical regions (specifically the pre-frontal cortex) and allow: (i) to bypass the dysfunctional basal ganglia, (ii) to stimulate the re-learning of the lost automatic movements, (iii) to reinforce the cortical mechanisms involved in the execution of the commands to move and, finally, (iv) to improve the patients’ mobility, balance, gait and posture [ 46 , 49 , 50 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%